Exploring wild alleles from Solanum pimpinellifolium with the potential to improve tomato flavor compounds. (September 2020) - Çolak, Nergiz Gürbüz; Eken, Neslihan Tek; Ülger, Mehmet; Frary, Anne; Doğanlar, Sami
Highlights: Tomato flavor components were assessed in a wild species population. A total of 85 QTLs were identified for individual sugar and organic acids. S. pimpinellifolium alleles can be used to improve flavor. Potential candidate genes were identified by examining genomic sequences. Abstract: Most consumers complain about the flavor of current tomato cultivars and many pay a premium for alternatives such as heirloom varieties. Breeding for fruit flavor is difficult because it is a quantitatively inherited trait influenced by taste, aroma and environmental factors. A lack of genetic diversity in modern tomato cultivars also necessitates exploration of new sources for flavor alleles. Wild tomato S. pimpinellifolium and inbred backcross lines were assessed for individual sugars and organic acids which are two of the main components of tomato flavor. S. pimpinellifolium was found to harbor alleles that could be used to increase glucose and fructose content and adjust acidity by altering malic and citric acid levels. Single nucleotide polymorphism markers were used to detect 14 quantitative trait loci (QTLs) for sugars and 71 for organic acids. Confirmation was provided by comparing map locations with previously identified loci. Thus, seven (50 %) of the sugar QTLs and 22 (31 %) of the organic acids loci were supported by analyses in other tomato populations. Examination of the genomic sequence containing the QTLs allowed identification of potential candidate genes for several flavor components.